1994
DOI: 10.1111/j.1443-1661.1994.tb00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cell Proliferation in Endoscopically Biopsied Specimens of Stomal Mucosa of the Gastric Remnant

Abstract: Carcinoma of the gastric remnant is thought to occur more commonly in the stomal than in the other areas, particularly following Billroth II surgery (BII). An attempt was made to determine the status of cell kinetics in the gastric remnant using endoscopically biopsied specimens, with assay of ornithine decarboxylase (ODC) activity and flow cytometric analysis of the cell cycle parameters. Fifty‐two partially gastrectomized patients were studied. Significantly higher ODC activity was recognized in the stomal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Based on the present results we suggest that there are different molecular pathways in carcinogenesis of the remnant stomach after surgery for benign disease compared with that after cancer surgery, as has been demonstrated in many clinical investigations (7,26). Furthermore, as Klump has suggested (39), the promoter methylation status may be a candidate marker for diagnosis and for clinically unapparent neoplastic alterations in patients with remnant stomach.…”
Section: Table IV Correlation Between P16 Protein Expression and P16supporting
confidence: 73%
See 1 more Smart Citation
“…Based on the present results we suggest that there are different molecular pathways in carcinogenesis of the remnant stomach after surgery for benign disease compared with that after cancer surgery, as has been demonstrated in many clinical investigations (7,26). Furthermore, as Klump has suggested (39), the promoter methylation status may be a candidate marker for diagnosis and for clinically unapparent neoplastic alterations in patients with remnant stomach.…”
Section: Table IV Correlation Between P16 Protein Expression and P16supporting
confidence: 73%
“…The influence of reflux of the duodenal juice on cancer development at anastomosis of the remnant stomach in animal models is well known (4). We have also observed the acceleration of glandular hypertrophy and cellular proliferation at anastomosis in clinical samples more predominantly in Billroth II type reconstruction, where reflux is more commonly found than in Billroth I type reconstruction (24)(25)(26). Kaminishi et al have reported that surgical denervation impairs the defense mechanism in the mucosa at the stump of the remnant stomach, leading to tumor development in experimental models (5).…”
Section: Discussionmentioning
confidence: 64%